Identifying the challenges in obtaining Green Building Index (GBI) Certification in construction industry / Izatul Farrita Mohd Kamar ... [et al.] - Izatul Farrita, Mohd Kamar; Lilawati, Ab Wahab; Nor Suzila, Lop; Noor Aishah, Mohammad Hamdan (2015)
Green Building Index (GBI) was the first tropical green tool design in the world developed by PertubuhanArkitek Malaysia (PAM) and Association of Consulting Engineers Malaysia (ACEM). GBI is Malaysia‟s industry recognized green rating tool for building to promote sustainability in the built environment and raise awareness among the construction industry and the public. The purpose of this research is to identify the challenges faced during obtaining the certification of Green Building Index (GBI). This research isalsocarried out to examine the problem of process regarding Green Building Index (GBI) certification. A mixed approach of literature review with questionnaire surveys was applied to achieve the objectives. The questionnaires were distributed to private developers in the Klang Valley who are involved in green building projects. The results indicated that most of the respondents agreed that operating and capital budgets are costly to develop green building. Furthermore, it showed that the most common problems regardingGBI certification is to select the person most responsible for GBI certification. However, Malaysia is still new in implementing green building that can achieve the classification of the GBI certification.